Effects of Brazilian wheat subsidies on income distribution and trade - Calegar, Geraldo M.; Schuh, George Edward (International Food Policy Research Institute, 1988)
Brazilian wheat policy as considered in this chapter consists of two relatively separate components: production policies and consumption policies. Both components derive from a number of national goals, including selfsufficiency in wheat supply, control of inflation, provision of cheap food for the urban population, and improvement in the distribution of income. The central government has maintained both a monopolistic and a monopsonistic role in the wheat market in order to implement its policy. The government is the sole importer and sole buyer from farmers and the only seller to the mills. Moreover, the government has maintained rigid control over prices at the producer, wholesale, and retail levels.